SISTEM PERINGATAN DINI SEBAGAI PENDUKUNG KINERJA PERUSAHAAN ASURANSI SYARIAH - Hariandy Hasbi; Bethani Suryawardani (University of Merdeka Malang, 2013)
The objective of this study was to investigate empirically the performance of islamic insurance companythrough the relationship and the impact of early warning system on the level of financial solvency. Thisresearch used secondary data period 2004-2011 from PT. Takaful Indonesia as one of islamic insurancecompany in Indonesia. Early warning system was reflected by aggregate surplus ratio, management cost ratio,and account receivable premium to surplus ratio, and also risk based capital ratio as a measure of insurancecompany solvability level. The result of this study indicated that the early warning system had a significantcontribution to the level of Islamic insurance company solvency, while the minimum level of Islamic insurancecompany solvency amounted 65.753% of the minimum regulation (120%).